Design of a THz-MEMS Frequency Selective Surface for Structural Health Monitoring - Pavia, J.P.; W. J . Otter; Otter, W.J.; S. Lucyszyn; Ribeiro, M. (META’16, the 7th International Conference on Metamaterials, Photonic Crystals and Plasmonics, 2016)
This paper characterizes the relationship between applied force and reflectance/transmittance of a terahertz frequency selective surface for use as a sensor in structural health monitoring. Numerical modelling of both the mechanical and electromagnetics, solving the elasticity equation and Maxwell’s equations, respectively, has been undertaken for a 3 layer device. The unit cell comprises of a metal cross wire embedded within a (hard) silicon substrate, interleaved with stacks of (soft) low density polyethylene.